Odpowiedzi

2010-01-28T17:11:34+01:00
A)
x(x-3)(x+1)-x³= 2-2x²
x(x²-3)-x³=2-2x²
x³ -3x -x³ = 2-2x²
-3x=2-2x²
-3x+2x²=2

b)
5(x-1)+3(x+2)(x-2)-2x²= x(6+x)
5x - 5 +3(x²-4)-2x²=6x + x²
5x - 5 +3x²-12-2x²=6x + x²
5x +3x²-2x²-6x -x² = 5+12
-x=17 /:(-1)
x=-17

;)
Najlepsza Odpowiedź!
2010-01-28T17:13:47+01:00
A) x(x-3)(x+1)-x³= 2-2x²
(x²-3x)(x+1)-x³=2-2x²
x³+x²-3x²-3x-x³=2-2x²
-2x²-3x+2x²=2
-3x=2 /:(-3)
x=-²/₃
b) 5(x-1)+3(x+2)(x-2)-2x²= x(6+x)
5x-5+(3x+6)(x-2)-2x²=6x+x²
5x-5+3x²-6x+6x-12-2x²=6x+x²
-x=17 /:(-1)
x=-17
2010-01-28T17:14:57+01:00
A)x=2
x²=2*2=4
2-2=2
odp. 2
b)x=2
5(x-1)+3(x+2)(x-2)-2x²= x(6+x)=2(6+2)=2*8=16